Penerapan Evaluasi Pembelajaran Tes Dan Non-Tes Pendidikan Agama Islam di Sekolah Menengah Kejuruan - Angga Widiyarto; Nurul Latifatul Inayati (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to (1) describe the implementation of the evaluation of Islamic education tests and non-tests at SMK Batik 2 Surakarta.  (2) Describe the constraints in the implementation of test and non-test PAI learning evaluation at Batik 2 Surakarta Vocational School.  The type of data analysis used is field data, in collecting data used interview techniques, observation, and documentation.  The method used in this research is descriptive analysis.  The findings from this study are that Batik 2 Surakarta Vocational School in PAI learning applies evaluation in the form of tests and non-tests, in the test section it is knowledge-based, meaning the assessment can be seen from the results of students' knowledge tests by oral or written tests, while for non-tests it can be seen from the results of the practical exam assessment.  Obstacles in the implementation of PAI learning evaluation at Batik 2 Surakarta Vocational School, in general, are due to the character of students who are classified as middle and affluent families.  In addition to evaluating learning outcomes in PAI, as in the case of test scores that are lacking or do not meet the KKM, a remedial will be held in the hope that the evaluation results will be able to meet the KKM that has been determined.